Enhancement of Ad hoc Networks Using Cloud Computing - Bhanot, D; Chaudhary, A (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we intend a protocol scheme for network mobility (NEMO) in ruinous scenarios assisted by cloud computing based on Ad-hoc networks. The proposed attempt tries to reduce the network burden on the mobile nodes and also minimize the link failures during hand over by availing cloud services while transmitting in between the nodes. This paper describes the route creation for the MANET as well as the route maintenance while maintaining the connectivity within the nodes. It also provides the proper mobility support in Ad Hoc mechanism. The introduction of cloud in MANET improves the quality .Thus an attempt is introduced to achieve the level of stability.